PELATIHAN KETRAMPILAN RAJUT, KERAMIK DAN VIDIOGRAFI - Iqbal Maimun Umar; Joni Nur Budi (Universitas Pelita Harapan, 2022)
Abstract The complexity of everyday life affects the emotional, and uncontrollable behavior of society. usually irrational in making instant decisions that result in bad results in his life. Patience and clear thinking can untangle complex and thorny issues into calmer ones. Peace of mind there needs to be life learning and enjoying the process in the face of life. Ceramic, Knitting and Vidiography Training is a CSR activity proposed in this period to train the community in conditioning taste problems that are sometimes not controlled. Knitting skills training is a skill that has a level of stress relief and a level of intelligence. Likewise for ceramics patience is needed to form the desired dimensions or create new shapes. The soft and elastic properties of clay materials will test participants' patience. Likewise for ceramics patience is needed to form the desired dimensions or create new shapes. The soft and elastic properties of clay materials will test participants' patience. In this case, participants are trained to be patient and focused until they succeed in creating the shape of a pot, mug, cup or bowl. Vidiography of activities that are not only carried out by one profession but the general public in their daily lives wants to document each of their activities. Basic videography knowledge can be used for socialization and publication in various media such as Instagram, Facebook, Youtube, Tweeter and so on. These three trainings are carried out in one UMN CSR program, to fill activities in the post-Covid 19 pandemic so that they can rise again to face challenges in the future.Keywords : csr, ceramics, knitting, vidiography, pandemicabstract in bahasaKompleksitas kehidupan sehari-hari mempengaruhi perilaku masyarakat yang emosional, dan tak terkendali. biasanya tidak rasional dalam mengambil keputusan yang instan sehingga berakibat yang kurang baik dalam kehidupannya. Kesabaran dan berfikir jernih dapat mengurai persoalan yang rumit dan pelik menjadi lebih tenang. Ketenangan jiwa perlu ada pembelajaran hidup dan menikmati proses dalam menghadapi hidup. Pelatihan Keramik, Rajut dan Vidiografi adalah kegiatan PKM yang diajukan dalam periode ini untuk melatih masyarakat dalam pengkondisian persoalan rasa yang kadang tidak terkontrol. Latihan ketrampilan rajut merupakan ketrampilan yang memiliki tingkat pereda stres dan tingkat kecerdasan. Demikian juga untuk keramik kesabaran dibutuhkan untuk membentuk dimensi yang diinginkan atau menciptakan bentuk baru. Sifat bahan lempung (clay) yang lunak dan elastis akan menguji kesabaran peserta. Dalam hal ini peserta dilatih sabar dan fokus hingga berhasil dalam menciptakan bentuk pot, mug, cangkir ataupun mangkok. Vidiografi kegiatan yang tidak hanya dilakukan oleh satu profesi tapi masyarakat umum dalam keseharian ingin mendokumentasikan setiap kegiatannya. Pengetahuan vidiografi dasar bisa digunakan untuk sosialisasi dan publikasi di berbagai media seperti Instagram, Facebook, Youtube, Tweeter dan lain sebagainya. Ketiga pelatihan ini dilaksanakan dalam satu program PKM UMN, untuk mengisi kegiatan di pasca pandemi Covid 19 supaya dapat bangkit lagi untuk menghadapi tantangan di masa depan. Kata Kunci : pkm, keramik, rajutan, vidiografi, pandemi